Analysis Of Monday Effect, Weekend Effect, and Rogalski Effect Anomalies Before And During The Covid-19 Pandemic Period (Study on LQ-45 Index Companies Listed on The Indonesia Stock Exchange) - Nadia Putri Kamila; Iis Duwinaeni; Akhmad Samsul Ulum; Inayah Risqi Alisa (Universitas Pekalongan, 2025)
The purpose of this research is to. (1) To find out the difference in stock returns on the Monday effect before and during the Covid-19 pandemic on the LQ-45 stock index listed on the Indonesia Stock Exchange. (2) To find out the differences in stock returns in Weekend effect before and during the Covid-19 pandemic on the LQ-45 stock index listed on the Indonesia Stock Exchange. (3) To find out the difference in stock returns on the Rogalski effect before and during the Covid-19 pandemic on the LQ-45 stock index listed on the Indonesia Stock Exchange. This research is an empirical study on Monday stock returns, Friday stock returns, and Monday stock returns in April with a comparative method. The sample used in this research is data daily stock returns of companies included in the LQ-45 period before (February 2019 – January 2020) and during (February 2020 – January 2021) the Covid-19 pandemic, namely 36 companies. The data analysis technique used was paired sample t-test for H1, H2 and H3. The results of the study show that: (H1) there is no significant difference between stock returns on Mondays before the Covid-19 pandemic and stock returns on Mondays during the Covid-19 pandemic on the Indonesia Stock Exchange from February 2019 to January 2021. ( H2) shows a significant difference between stock returns on Friday before the Covid-19 pandemic and stock returns on Monday during the Covid-19 pandemic on the Indonesia Stock Exchange from February 2019 to January 2021. (H3) shows a significant difference between stock returns on Mondays in April before the Covid-19 pandemic and stock returns on Mondays during the Covid-19 pandemic on the Indonesia Stock Exchange in February 2019 to January 2021. The purpose of this research is to. (1) To find out the difference in stock returns on the Monday effect before and during the Covid-19 pandemic on the LQ-45 stock index listed on the Indonesia Stock Exchange. (2) To find out the differences in stock returns in Weekend effect before and during the Covid-19 pandemic on the LQ-45 stock index listed on the Indonesia Stock Exchange. (3) To find out the difference in stock returns on the Rogalski effect before and during the Covid-19 pandemic on the LQ-45 stock index listed on the Indonesia Stock Exchange. This research is an empirical study on Monday stock returns, Friday stock returns, and Monday stock returns in April with a comparative method. The sample used in this research is data daily stock returns of companies included in the LQ-45 period before (February 2019 – January 2020) and during (February 2020 – January 2021) the Covid-19 pandemic, namely 36 companies. The data analysis technique used was paired sample t-test for H1, H2 and H3. The results of the study show that: (H1) there is no significant difference between stock returns on Mondays before the Covid-19 pandemic and stock returns on Mondays during the Covid-19 pandemic on the Indonesia Stock Exchange from February 2019 to January 2021. ( H2) shows a significant difference between stock returns on Friday before the Covid-19 pandemic and stock returns on Monday during the Covid-19 pandemic on the Indonesia Stock Exchange from February 2019 to January 2021. (H3) shows a significant difference between stock returns on Mondays in April before the Covid-19 pandemic and stock returns on Mondays during the Covid-19 pandemic on the Indonesia Stock Exchange in February 2019 to January 2021.